2011
DOI: 10.1590/s0100-204x2011001000038
|View full text |Cite
|
Sign up to set email alerts
|

Recria de borregas sob diferentes métodos de pastoreio em azevém anual em sucessão a lavoura

Abstract: Resumo -O objetivo deste trabalho foi avaliar a recria de borregas em pastagem de azevém anual (Lolium multiflorum) em sucessão a lavouras de milho ou soja, manejadas em intensidades de pastejo moderada ou baixa, com métodos de pastoreio rotativo ou contínuo. Utilizou-se o delineamento experimental de blocos ao acaso em arranjo fatorial 2 intensidades x 2 métodos de pastoreio, com quatro repetições. Não houve interação entre os métodos e as intensidades de pastejo. A intensidade de pastejo baixa determinou mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
2
2
0
3
Order By: Relevance
“…O aumento da altura das plantas com a adubação nitrogenada está correlacionado com maiores taxas de alongamento de colmos e folhas, estimuladas pela aplicação de N. Na avaliação de genótipos, o estudo da altura torna-se importante, pois, segundo Macari et al (2011) existe alta correlação entre altura e a massa de forragem o que permite estabelecer guias de manejo de pastagem usando a altura como referência, dada a sua facilidade de compreensão, análise e aplicação.…”
Section: Discussionunclassified
“…O aumento da altura das plantas com a adubação nitrogenada está correlacionado com maiores taxas de alongamento de colmos e folhas, estimuladas pela aplicação de N. Na avaliação de genótipos, o estudo da altura torna-se importante, pois, segundo Macari et al (2011) existe alta correlação entre altura e a massa de forragem o que permite estabelecer guias de manejo de pastagem usando a altura como referência, dada a sua facilidade de compreensão, análise e aplicação.…”
Section: Discussionunclassified
“…Macari et al (2011) found that grazing sheep in an area with ryegrass did not affect the productivity of corn and soybean grown in succession, regardless of the intensity and grazing method used. Tracy and Zhang (2008) found not only that the presence of cattle in agricultural areas did not negatively affect soil properties and corn productivity in a five-year trial period but also that their presence conferred benefits, such as improved soil quality, due to the increased organic matter and reduced animal feeding costs during the winter.…”
Section: Introductionmentioning
confidence: 91%
“…Yield data from these experimental areas have shown that summer crops do not change or are slightly improved with grazing of cover crops, in addition to animal production during the pasture phase in the winter. Production data from crops and livestock can be found in Martins, Anghinoni, Kunrath, and Carvalho (2015) for São Miguel das Missões, from Sandini (2009), Andreolla (2010), De Pellegrini et al (2010)), Sandini et al (2011), Sartor (2012) and Andreolla, Moraes, Bonini, Deiss, et al (2014) for Guarapuava, and Lunardi, Trein, Cauduro, Maria, and Barbosa (2008), Barth‐Neto (2015) and Macari et al (2011) for Eldorado do Sul. Therefore, we conclude that more food was produced on the same land unit with an equal level of nutrient input.…”
Section: Discussionmentioning
confidence: 99%